Hardened cement and precast concrete panels

The cement-hardened body, formulated with specific components and particle size distributions, addresses the challenge of achieving both excellent abrasion resistance and suitable fluidity for cement compositions, enhancing the workability and filling properties during installation.

JP7653337B2Active Publication Date: 2025-03-28TAIHEIYO CEMENT CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021155735
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-24
Publication Date
2025-03-28
Estimated Expiration
2041-09-24

AI Technical Summary

Technical Problem

Cement-hardened bodies used for paving require both excellent abrasion resistance and suitable fluidity of the cement composition for installation, which existing technologies struggle to achieve simultaneously.

Method used

A cement-hardened body composed of a cement composition containing cement, silica fume, inorganic powder, fine aggregate, hard sand, high-performance water reducing agent, antifoaming agent, and water, with specific particle size distributions and content ratios of hard sand relative to fine aggregate, which enhances both wear resistance and flowability.

Benefits of technology

The solution provides a cement-hardened body with excellent abrasion resistance and suitable fluidity for installation, ensuring sufficient workability and filling properties during application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653337000003
    Figure 0007653337000003
  • Figure 0007653337000004
    Figure 0007653337000004
  • Figure 0007653337000001
    Figure 0007653337000001
Patent Text Reader

Abstract

To provide a cement composition excellent in abrasion resistance with flowability suitable for construction.SOLUTION: A hardened body of a cement composition comprises at least a cement, a silica fume, inorganic powder, a fine aggregate, hard sand, a high-performance water reducer, a defoamant, and water. Compressive strength thereof is 300 N / mm2 or more; a maximum grain size of the fine aggregate is 1.2 mm or less; hardness of the hard sand is higher than that of the fine aggregate; in a grain size of the hard sand, a 10% weight cumulative grain size is 1.2 mm or more, and a 90% weight cumulative grain size is 5.0 mm or less; and a content ratio of the hard sand to the total amount of the fine aggregate and hard sand is 30% or more and 70% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hardened cement product and a precast concrete slab. [Background technology]

[0002] Wear caused by running tires is a problem for roadway pavements and railway tracks on which trains equipped with rubber tires run. When concrete is used for these pavements and tracks, the higher the strength of the concrete, the higher the resistance to wear, and the longer the service life can be expected. From this perspective, Patent Document 1 proposes a concrete pavement with high bending strength and wear resistance. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-179927 A Summary of the Invention [Problem to be solved by the invention]

[0004] In addition to satisfying the requirements for a hardened cement product for paving, it is also preferable that the properties of the cement composition are suitable for application. In particular, since fluidity affects application and filling properties, it is preferable that the fluidity of the cement composition is suitable for application.

[0005] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a hardened cement product and a precast concrete slab which not only have excellent abrasion resistance but also have a cement composition having fluidity suitable for construction. [Means for solving the problem]

[0006] (1) In order to achieve the above object, the present invention provides the following: That is, the hardened cement product of the present invention is a hardened cement composition containing at least cement, silica fume, inorganic powder, fine aggregate, hard sand, a high-performance water reducing agent, a defoaming agent, and water, and has a compressive strength of 300 N / mm 2 the maximum particle size of the fine aggregate is 1.2 mm or less, the hardness of the hard sand is higher than that of the fine aggregate, the particle size of the hard sand is such that the 10% cumulative particle size by weight is 1.2 mm or more and the 90% cumulative particle size by weight is 5.0 mm or less, and the content of the hard sand in the total amount of the fine aggregate and the hard sand is 30% or more and 70% or less.

[0007] This not only provides excellent abrasion resistance, but also provides the cement composition with fluidity suitable for application.

[0008] (2) The hardened cement product of the present invention is characterized in that it further contains coarse aggregate having a maximum particle size of more than 2.5 mm and not more than 20 mm, thereby improving dimensional stability.

[0009] (3) In the hardened cement product of the present invention, the hard sand has a new Mohs hardness of 8 or more. This improves abrasion resistance.

[0010] (4) In the hardened cement product of the present invention, the hard sand is one or more selected from quartz, alumina, and silicon carbide. This provides sufficient fluidity of the cement composition when the hardened cement product is produced. In addition, the hardened cement product can easily achieve the abrasion resistance required for paving purposes.

[0011] (5) In the hardened cement product of the present invention, the cement comprises particles of grinded moderate-heat Portland cement or low-heat Portland cement, and the grinded particles have a 50% cumulative particle size by volume of 10 to 18 μm and a Blaine specific surface area of ​​2100 to 2900 cm. 2 / g.

[0012] This not only improves the fluidity of the cement composition, but also improves the strength and abrasion resistance of the hardened cement body.

[0013] (6) The hardened cement body of the present invention is characterized in that it contains one or more fibers selected from metal fibers, organic fibers, and carbon fibers, and the fiber content is 4 volume % or less, thereby improving the strength and fracture energy of the hardened cement body while maintaining the fluidity and workability of the cement composition.

[0014] (7) The precast concrete slab of the present invention is characterized by comprising the hardened cement body according to any one of (1) to (6) above. In manufacturing such a precast concrete slab, the cement composition constituting the precast concrete slab has excellent fluidity and is therefore suitable for producing the precast concrete slab. In addition, the precast concrete slab has excellent wear resistance. Effect of the Invention

[0015] As described above, according to the present invention, not only is the abrasion resistance excellent, but the fluidity of the cement composition is suitable for application, and therefore the cement has sufficient application properties and filling properties when applied. [Brief description of the drawings]

[0016] [Figure 1] 1 is a front view showing an example of a polishing processing apparatus, partially including a cross section cut in a direction perpendicular to the rotation axis of a rotor. [Diagram 2] 1 is a table showing the formulation of a cement composition in each example and each comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] As a result of intensive research, the inventors of the present invention have invented a hardened cement product that is not only excellent in abrasion resistance but also has a flowability of the cement composition suitable for construction by controlling the particle size and content of hard sand, which is harder than fine aggregate. Hereinafter, an embodiment of the present invention will be described.

[0018] [Composition of hardened cement paste] The hardened cement product of the present invention is a hardened cement composition containing at least cement, silica fume, inorganic powder, fine aggregate, hard sand, a high-performance water reducing agent, a defoaming agent, and water.

[0019] (cement) The cement used in the present invention is not particularly limited, and examples thereof include various types of Portland cement such as ordinary Portland cement, early strength Portland cement, extra early strength Portland cement, moderate heat Portland cement, sulfate resistant Portland cement, low heat Portland cement, etc. Among these, moderate heat Portland cement or low heat Portland cement is preferred because the fluidity of the cement composition is high.

[0020] The cement used in the present invention contains particles of moderate heat Portland cement or low heat Portland cement that have been polished, and the 50% volume cumulative particle size of the cement is 10 to 18 μm and the Blaine specific surface area of ​​the cement is 2100 to 2900 cm 2 / g. The polished particles have a rounded shape of the angular surface of the cement particles, and more preferably contain coarse particles with a particle size of 20 μm or more and fine particles with a particle size of less than 20 μm produced by the polishing treatment. This increases the fluidity of the cement composition and increases the compressive strength of the hardened cement body.

[0021] The upper limit of the particle size of the coarse particles is not particularly limited, but taking into consideration the general particle size of polished cement, it is preferably 200 μm or less, and more preferably 100 μm or less, since this increases the compressive strength of the hardened cement body.

[0022] The lower limit of the particle size of the microparticles is not particularly limited, but is preferably 0.1 μm or more, more preferably 0.5 μm or more, since this increases the fluidity of the cement composition and improves the workability when producing a hardened cement body.

[0023] The 50% volume cumulative particle size of the polished cement is preferably 10 to 18 μm, more preferably 12 to 16 μm, and the Blaine specific surface area is preferably 2100 to 2900 cm 2 / g, more preferably 2200 to 2700 cm 2 / g.

[0024] Since the 50% volume cumulative particle size is 10 μm or more, the fluidity of the cement composition is high, and since it is 18 μm or less, the compressive strength of the hardened cement body is higher. In addition, the Blaine specific surface area is 2100 cm 2 Since the viscosity is 2,900 cm2 / g or more, the compressive strength of the hardened cement body becomes higher, and since the viscosity is 2,900 cm2 / g or less, the fluidity of the cement composition is improved.

[0025] The polishing treatment can be carried out using a known polishing treatment device capable of polishing moderate heat Portland cement or low heat Portland cement. For example, a high-speed air current agitator can be used as the polishing treatment device.

[0026] Hereinafter, a polishing process using a high-velocity air current agitator as the polishing processing device will be described in detail with reference to FIG.

[0027] The cement used in the present invention is charged from the charging port 14 at the top of the polishing processing device 10 with the on-off valve 18 open, and then the on-off valve 18 is closed. The charged cement enters the circulation circuit 13 from an opening provided in the middle of the circulation circuit 13, and then enters the collision chamber 17, which is a space for accommodating the object to be treated, from the outlet 13b of the circulation circuit 13.

[0028] After the cement is poured in, rotor (rotating body) 11 disposed inside stator 16, which is a fixed body, is rotated at high speed, whereby a high-speed airflow is generated by rotor 11 and blades 12 fixed to rotor 11, and the cement in collision chamber 17 is stirred. During this stirring, cement particles enter circulation circuit 13 from inlet 13a of circulation circuit 13 provided in collision chamber 17, and are poured again into collision chamber 17 from outlet 13b of circulation circuit 13 provided in the center of collision chamber 17, where they are circulated. In addition, the arrows shown by dotted lines in Fig. 1 indicate the flow of cement particles, coarse particles generated by the polishing process, and fine particles.

[0029] As the cement particles are stirred, they collide with the inner wall surface of the collision chamber 17, the rotor 11, and the blades 12, and also with each other, resulting in the cement particles being polished, with the angular parts of the particle surface becoming rounded, resulting in coarse particles with a particle size of 20 μm or more and fine particles with a particle size of less than 20 μm.

[0030] The rotation speed of the rotor 11 is preferably 3000 to 4200 rpm, and more preferably 3500 to 4000 rpm. Since the rotation speed of the rotor 11 is 3000 rpm or more, the fluidity of the cement composition is improved, and when the rotation speed exceeds 4200 rpm, the effect of improving the fluidity of the cement composition is saturated.

[0031] The polishing time is preferably 10 to 60 minutes, more preferably 20 to 50 minutes, further preferably 20 to 40 minutes, and further preferably 20 to 30 minutes. When the polishing time is 10 minutes or more, the fluidity of the cement composition is improved, and when it exceeds 60 minutes, the effect of improving the fluidity of the cement composition is saturated.

[0032] Finally, the resulting polished product (a mixture of coarse and fine particles) is discharged from the discharge port 15 by opening the discharge valve 19.

[0033] (Silica fume) The BET specific surface area of ​​the silica fume used in the present invention is 15 to 25 m 2 / g, preferably 17 to 23 m 2 / g, more preferably 18 to 22m 2 / g. The BET specific surface area is 15m 2 / g or more, the compressive strength of the hardened cement can be improved, and 2 / g or less, it is possible to suppress a decrease in the fluidity of the cement composition.

[0034] (Inorganic powder) The inorganic powder may be one or more of quartz powder (silica powder), volcanic ash, slag powder, limestone powder, feldspar powder, mullite powder, alumina powder, silica sol, carbide powder, nitride powder, and classified or crushed fly ash. The inorganic powder preferably has a 50% cumulative volume particle size of 0.8 to 5 μm.

[0035] Among these, quartz powder or fly ash is preferable because it improves the fluidity of the cement composition and increases the compressive strength of the hardened cement body. In this specification, the inorganic powder having a 50% volume cumulative particle size of 0.8 to 5 μm does not include cement.

[0036] The inorganic powder used in the present invention has a 50% cumulative particle size by volume of 0.8 to 5 μm, preferably 1 to 5 μm, more preferably 1.1 to 3.5 μm, and even more preferably 1.2 μm or more and less than 3 μm. When the particle size is larger than 0.8 μm, the fluidity of the cement composition is improved, and when the particle size is smaller than 5 μm, the compressive strength of the hardened cement body is improved.

[0037] The 50% volume cumulative particle size of the inorganic powder can be determined using a commercially available particle size distribution measuring device such as "Microtrac HRA Model 9320-X100" (manufactured by Nikkiso Co., Ltd.).

[0038] The 50% volume cumulative particle size is, for example, 20 cm of ethanol, which is the solvent in which the sample is dispersed. 30.06 g of a sample is added to the mixture, and ultrasonically dispersed for 90 seconds using an ultrasonic dispersing device (for example, product name "US300" manufactured by Nippon Seiki Seisakusho), and then a cumulative particle size curve of the particles in the dispersion is created and determined using a particle size distribution measuring device.

[0039] The maximum particle size of the inorganic powder is preferably 15 μm or less, more preferably 14 μm or less, and even more preferably 13 μm or less, because the compressive strength of the hardened cement body is higher. Also, the 95% volume cumulative particle size of the inorganic powder is preferably 8 μm or less, more preferably 7 μm or less, and even more preferably 6 μm or less, because the compressive strength of the hardened cement body is higher.

[0040] The inorganic powder used in the present invention is preferably an inorganic powder mainly composed of SiO2, such as quartz powder. The content of SiO2 in the inorganic powder is preferably 50 mass% or more, more preferably 60 mass% or more, and even more preferably 70 mass% or more. If the content of SiO2 in the inorganic powder is 50 mass% or more, the compressive strength of the hardened cement body becomes higher.

[0041] The cement content in the cement composition used in the present invention is 55 to 65 volume %, preferably 57 to 63 volume %, based on 100 volume % of the total of cement, silica fume, and inorganic powder. When the cement content in the cement composition is 55 volume % or more, the compressive strength of the cement hardened body is improved, and when it is 65 volume % or less, the fluidity of the cement composition is improved.

[0042] The content of silica fume in the cement composition used in the present invention is 5 to 25 volume %, preferably 7 to 25 volume %, based on 100 volume % of the total of cement, silica fume, and inorganic powder. When the content is 5 volume % or more, the compressive strength of the hardened cement body is improved, and when it is 25 volume % or less, the fluidity of the cement composition is improved.

[0043] The content of the inorganic powder in the cement composition used in the present invention is 15 to 35 volume %, preferably 17 to 33 volume %, based on 100 volume % of the total of the cement, silica fume, and inorganic powder. If the content is 15 volume % or more, the compressive strength of the hardened cement body is improved, and if it is 35 volume % or less, the fluidity of the cement composition is improved.

[0044] (fine aggregate) The fine aggregate used in the present invention may be one or more selected from river sand, land sand, sea sand, crushed sand, silica sand, recycled fine aggregate, and artificial fine aggregate such as slag fine aggregate or fired fine aggregate obtained by firing fly ash or the like.

[0045] The maximum particle size of the fine aggregate is 1.2 mm or less, preferably 1.1 mm or less, and more preferably 1.0 mm or less. Since the maximum particle size is 1.2 mm or less, the compressive strength of the hardened cement paste is increased.

[0046] The particle size distribution of the fine aggregate improves the fluidity of the cement composition and increases the compressive strength of the hardened cement body, so that the content of aggregate with a particle size of 0.6 mm or less is preferably 95 mass% or more, the content of aggregate with a particle size of 0.3 mm or less is preferably 40 to 50 mass%, and the content of aggregate with a particle size of 0.15 mm or less is 6 mass% or less.

[0047] The content of fine aggregate in the cement composition is preferably 20 to 40 volume %, more preferably 22 to 38 volume %, further preferably 30 to 37 volume %, and particularly preferably 32 to 36 volume %. When the content of fine aggregate in the cement composition is 20 volume % or more, the calorific value of the cement composition is small and the shrinkage of the hardened cement body is small, and when it is 40 volume % or less, the compressive strength of the hardened cement body is high.

[0048] (High performance water reducing agent) The high performance water reducing agent used in the present invention is at least one selected from high performance water reducing agents such as naphthalenesulfonic acid-based, melamine-based, and polycarboxylic acid-based, etc. Among these, polycarboxylic acid-based high performance water reducing agents are preferred because they improve the fluidity of the cement composition and increase the compressive strength of the hardened cement body.

[0049] The mixing ratio of the high performance water reducing agent is preferably 0.2 to 1.5 parts by mass, more preferably 0.4 to 1.2 parts by mass, calculated as solid content, per 100 parts by mass of the total of cement, silica fume, and inorganic powder. When the mixing ratio of the high performance water reducing agent is 0.2 parts by mass or more, the water reducing performance is improved and the fluidity of the cement composition is improved, and when it is 1.5 parts by mass or less, the compressive strength of the hardened cement body is increased.

[0050] (Antifoaming agent) The defoaming agent used in the present invention may be a commercially available product, and the mixing ratio of the defoaming agent is preferably 0.001 to 0.1 parts by mass, more preferably 0.01 to 0.07 parts by mass, and even more preferably 0.01 to 0.05 parts by mass, relative to 100 parts by mass of the total of cement, silica fume, and inorganic powder. Since the mixing ratio of the defoaming agent is 0.001 parts by mass or more, the strength development of the cement composition is improved, and when it exceeds 0.1 parts by mass, the effect of improving the strength development of the cement composition is saturated.

[0051] (Hard sand) The hard sand used in the present invention is harder than fine aggregate, with a 10% cumulative particle size by weight of 1.2 mm or more and a 90% cumulative particle size by weight of 5.0 mm or less. The hard sand preferably has a new Mohs hardness of 8 or more. The hard sand is preferably one or more types selected from quartz, alumina, and silicon carbide. Since the hard sand has a 10% cumulative particle size by weight of 1.2 mm or more, the fluidity of the cement composition is suitable for application, and since the hard sand has a 90% cumulative particle size by weight of 5.0 mm or less, it has the wear resistance required for a paving cement hardened body.

[0052] The 10% cumulative particle size by weight of hard sand is 1.2 mm or more, as can be confirmed by the fact that less than 10% of the hard sand passes through a 1.2 mm sieve. Also, the 90% cumulative particle size by weight of hard sand is 5.0 mm or less, as can be confirmed by the fact that more than 90% of the hard sand passes through a 5.0 mm sieve.

[0053] The particle size of the hard sand is adjusted as follows: First, the hard sand is sieved according to JIS A 1102 "Sieving test method for aggregates" until the amount of hard sand passing through the 5.0 mm sieve in one minute is 0.1% or less of the total hard sand. As with the 5.0 mm sieve, sieving is also repeated for the 2.5 mm and 1.2 mm sieves until the amount of hard sand passing through the 5.0 mm sieve in one minute is 0.1% or less of the total hard sand. The sieved sand is then mixed so that the 10% cumulative particle size by weight is 1.2 mm or more and the 90% cumulative particle size by weight is 5.0 mm or less.

[0054] The content of the hard sand used in the present invention is 30% or more and 70% or less of the total amount of fine aggregate and hard sand in the concrete. Since the content of the hard sand is 30% or more, the abrasion resistance required for a paving cement hardened body is satisfied, and since it is 70% or less, the fluidity of the cement composition is suitable for construction.

[0055] In the above, the hard sand is configured so that the 10% weight cumulative particle size is 1.2 mm or more, the 90% weight cumulative particle size is 5.0 mm or less, and the hard sand content of the total amount of fine aggregate and hard sand is 30% to 70%, but the following configuration may also be used by using a sieve.

[0056] When the particle size distribution of the fine aggregate is 100% passing through a 10 mm sieve, 90% to 100% passing through a 5.0 mm sieve, 80% to 100% passing through a 2.5 mm sieve, 50% to 90% passing through a 1.2 mm sieve, 25% to 65% passing through a 0.6 mm sieve, 10% to 35% passing through a 0.3 mm sieve, and 2% to 15% passing through a 0.15 mm sieve, the hard sand is mixed so as to replace the fine aggregate equivalent to the 1.2 mm to 5.0 mm portion.

[0057] (fiber) The cement composition used in the present invention may contain one or more types of fibers selected from metal fibers, organic fibers, and carbon fibers, since the bending strength, fracture energy, etc. of the hardened cement body are improved. The fiber content in the cement composition is preferably 4 vol% or less, more preferably 3 vol% or less, further preferably 0.3 to 2.5 vol%, and particularly preferably 0.5 to 2.3 vol%. Since the fiber content in the cement composition is 4 vol% or less, the bending strength, fracture energy, etc. of the hardened cement body are improved without decreasing the fluidity and workability of the cement composition.

[0058] Examples of the metal fibers include steel fibers, stainless steel fibers, amorphous fibers, etc. Among these, steel fibers are preferable because of their excellent strength, cost, and availability.

[0059] The dimensions of the metal fibers are preferably 0.01-1.0 mm in diameter and 2-30 mm in length, more preferably 0.05-0.5 mm in diameter and 5-25 mm in length, since this prevents separation of the metal fibers in the cement composition and improves the bending strength of the hardened cement body. The aspect ratio of the metal fibers (fiber length / fiber diameter) is preferably 20-200, more preferably 40-150.

[0060] Furthermore, the shape of the metal fibers is preferably spiral or wavy, which can impart physical adhesive strength, rather than straight. If the metal fibers are spiral or other shapes, the metal fibers and the matrix secure stress while being pulled out, improving the bending strength of the hardened cement body.

[0061] The organic fibers may be any fibers that can withstand the heating in the method for producing a hardened cement body of the present invention described below, and examples thereof include aramid fibers, polyparaphenylene benzobisoxazole fibers, polyethylene fibers, polyallylate fibers, and polypropylene fibers.

[0062] Examples of the carbon fiber include PAN-based carbon fiber and pitch-based carbon fiber.

[0063] The dimensions of the organic fibers and carbon fibers are preferably 0.005 to 1.0 m in diameter and 2 to 30 mm in length, more preferably 0.01 to 0.5 mm in diameter and 5 to 25 mm in length, in order to prevent separation of the fibers in the cement composition and to improve the fracture energy of the hardened cement body. The aspect ratio of the organic fibers and carbon fibers (fiber length / fiber diameter) is preferably 20 to 200, more preferably 30 to 150.

[0064] (water) Tap water or the like can be used as the water, and the mixing ratio of water is preferably 10 to 20 parts by mass, more preferably 11 to 18 parts by mass, and even more preferably 14 to 16 parts by mass, per 100 parts by mass of the total of cement, silica fume, and inorganic powder. When the mixing ratio of water is 10 parts by mass or more, the fluidity of the cement composition is improved, and when it is 20 parts by mass or less, the compressive strength of the hardened cement body is increased.

[0065] (coarse aggregate) The cement composition of the present invention may contain coarse aggregate having a maximum particle size of more than 2.5 mm and not more than 20 mm.

[0066] The coarse aggregate may be one or more selected from fine aggregates such as river sand, mountain sand, land sand, sea sand, crushed sand, silica sand, recycled fine aggregate, and artificial fine aggregates such as fired fine aggregates obtained by firing slag fine aggregate, fly ash, etc., as well as river gravel, mountain gravel, land gravel, crushed stone, recycled coarse aggregate, and artificial coarse aggregates such as fired coarse aggregates obtained by firing slag coarse aggregate, fly ash, etc.

[0067] The maximum particle size of the coarse aggregate is preferably 20 mm or less, more preferably 15 mm or less. Since the maximum particle size of the coarse aggregate is 20 mm or less, the strength development of the cement composition is improved, for example, up to 300 N / mm 2 It is possible to achieve a compressive strength of the above.

[0068] The maximum particle size of the coarse aggregate is preferably more than 2.5 mm, and more preferably 5 mm or more. In this specification, the "maximum particle size" of the coarse aggregate refers to the particle size of the coarse aggregate represented by the nominal size of the smallest sieve among sieves through which 90% by mass or more of the entire coarse aggregate passes (this is generally known as the definition of the maximum particle size of coarse aggregate).

[0069] The minimum particle size of the coarse aggregate is preferably a value exceeding the maximum particle size of the fine aggregate, more preferably 2 mm or more, further preferably 3 mm or more, particularly preferably 4 mm or more, and extremely preferably 5 mm or more. In this specification, the minimum particle size of the coarse aggregate refers to the particle size of the coarse aggregate when it reaches 15% by mass of the entire coarse aggregate when accumulated from the minimum particle size to the maximum particle size of the coarse aggregate.

[0070] In the present invention, the total content of fine aggregate and coarse aggregate in the hardened cement body is preferably 25 to 40 volume %, more preferably 28 to 38 volume %, and further preferably 30 to 36 volume %. When the total content of fine aggregate and coarse aggregate in the hardened cement body is 25 volume % or more, the heat generation amount and shrinkage amount of the hardened cement body are small, and when it is 40 volume % or less, the strength development of the hardened cement body is improved.

[0071] The content of the coarse aggregate in the total of the fine aggregate and the coarse aggregate is preferably 40% by volume or less, more preferably 30% by volume or less, and further preferably 25% by volume or less. Since the content of the coarse aggregate in the total of the fine aggregate and the coarse aggregate is 40% by volume or less, the strength expression such as the compressive strength of the hardened cement body is improved.

[0072] The compressive strength of the hardened cement body obtained by hardening the cement composition containing the coarse aggregate is preferably 300 N / mm 2 More preferably, 320N / mm 2 More preferably, 340N / mm 2 More preferably, 360N / mm 2 That's all.

[0073] (Cement composition (mortar) and physical properties of hardened cement) The flow value before hardening of mortar made of the cement composition (not including coarse aggregate) is preferably 230 mm or more, more preferably 250 mm or more, as measured by the method described in "11. Flow test" of JIS R 5201 "Physical test methods for cement" omitting the 15 dropping motions (hereinafter referred to as "zero-pump flow value"). A flow value of 230 mm or more improves the workability when producing a hardened cement body. The concrete slump flow test was performed in accordance with JIS A 1150:2007. When the cement composition contains coarse aggregate, the zero-pump flow value is preferably 450 mm or more, more preferably 500 mm or more.

[0074] The compressive strength of the hardened cement body is preferably 300N / mm 2 More preferably, 350N / mm 2 More preferably, 400N / mm 2 In addition, when the cement composition contains coarse aggregate, the compressive strength of the hardened cement body is preferably 300 N / mm 2 More preferably, 320N / mm 2 More preferably, 360N / mm 2 That's all.

[0075] [Composition of precast concrete slab] The precast concrete slab of the present invention includes at least the above-mentioned hardened cement body. In addition, the precast concrete slab may include a joint structure for joining the precast concrete slabs to each other, in addition to the hardened cement body.

[0076] [Manufacturing method of hardened cement] The method for producing the hardened cement body of the present invention includes (A) a molding step, (B) a room temperature curing step, (C) a heat curing step, and (D) a high temperature heating step.

[0077] The method for producing a hardened cement product will be explained below by dividing it into steps (A) to (E). Note that steps (A) to (D) are essential steps in the present invention, and step (E) is an optional step.

[0078] (A) Molding process The molding step is a step of casting the cement composition into a formwork to obtain an unhardened molded body. The method of kneading the cement composition before casting and the device used for kneading are not particularly limited, and an omni mixer, a pan mixer, a biaxial mixer, a tilting mixer, etc. can be used. Furthermore, the method of casting and molding is also not particularly limited. In the molding step, the air bubbles in the unhardened cement composition are reduced or removed, and the strength development of the hardened concrete structure is further improved.

[0079] Methods for reducing or removing air bubbles in a cement composition include the following methods (i) to (iii). (i) A method in which the cement composition is mixed under reduced pressure (ii) A method in which the mixed cement composition is depressurized and degassed before being poured into a formwork. (iii) A method in which the cement composition is poured into a formwork and then degassed by reducing the pressure.

[0080] (B) Room temperature curing process The room temperature curing step is a step in which the uncured molded body is sealed and cured or cured in air at 10 to 40°C, preferably 15 to 30°C, for 24 hours or more, more preferably 24 to 72 hours, and even more preferably 24 to 48 hours, and then demolded to obtain a cured molded body.

[0081] If the curing temperature is 10°C or higher, the curing time can be shortened. Since the curing temperature is 40°C or lower, the compressive strength of the hardened cement body is higher. Also, since the curing time is 24 hours or longer, defects such as chips and cracks are less likely to occur in the hardened molded body when it is demolded.

[0082] In the room temperature curing step, the compressive strength of the hardened molded body is preferably 20 to 100 N / mm 2 , more preferably 30 to 80N / mm 2When the compressive strength is 20 to 100 N / mm 2 If the compressive strength is 100N / mm or more, defects such as chipping or cracking are unlikely to occur in the hardened molded body when it is demolded. 2 Because of the above, in the water absorption step described below, the hardened molded body can absorb water with little effort.

[0083] (C)Heat curing process The heat curing step is a step in which the hardened molded body obtained in the previous step is subjected to either or both of steam curing or hot water curing at preferably 70°C or higher but lower than 100°C, more preferably 75 to 95°C, and more preferably 80 to 92°C, for 6 hours or more, and autoclave curing at preferably 100 to 200°C, more preferably 160 to 190°C, for 1 hour or more, to obtain a hardened body after heat curing.

[0084] In the heat curing step, when only steam curing or hot water curing is performed, the curing time is preferably 24 hours or more, more preferably 24 to 96 hours, and even more preferably 36 to 72 hours. When only autoclave curing is performed, the curing time is preferably 8 to 60 hours, and more preferably 12 to 48 hours. When both steam curing or hot water curing and autoclave curing are performed (for example, when autoclave curing is performed after steam curing or hot water curing), the curing time for steam curing or hot water curing is preferably 6 to 72 hours, and more preferably 12 to 48 hours, and the curing time for autoclave curing is preferably 1 to 24 hours, and more preferably 4 to 18 hours.

[0085] In the heat curing step, if the curing temperature and curing time are within the above ranges, the curing time can be shortened and the compressive strength of the hardened cement body can be improved.

[0086] (D) High temperature heating process The high-temperature heating step is a step in which the hardened body after heat curing is heated preferably at 150 to 200°C, more preferably at 170 to 190°C, for 24 hours or more, preferably for 24 to 72 hours, more preferably for 36 to 48 hours (excluding heating due to autoclave curing) to obtain a hardened cement body.

[0087] The heating in the high-temperature heating step is usually performed in a dry atmosphere, in other words, without artificially supplying water or water vapor. The heating time can be shortened by heating at a temperature of 150°C or higher, and the compressive strength of the hardened cement body is improved by heating at a temperature of 200°C or lower. In addition, the heating time of 24 hours or more improves the compressive strength of the hardened cement body.

[0088] (E) Water absorption process The water absorption step is an optional step between the room temperature curing step and the heat curing step in which the hardened molded body obtained in the room temperature curing step is allowed to absorb water.

[0089] The method for making the cured molded body absorb water includes the following methods (i) to (v). (i) A method in which a molded body is immersed in water under reduced pressure (ii) A method in which the molded body is immersed in boiling water and the water temperature is lowered to 40°C or less. (iii) A method in which the molded body is immersed in boiling water, then removed from the boiling water and immersed in water at 40°C or lower. (iv) A method in which a molded body is immersed in water under pressure (v) A method of immersing a molded body in an aqueous solution containing an agent that improves the water permeability of the molded body.

[0090] And, regarding (i) and (ii) above, (i) The method of immersing the molded body in water under reduced pressure uses equipment such as a vacuum pump and a large reduced pressure vessel. (ii) The method of immersing the molded body in boiling water may utilize equipment such as a high-temperature, high-pressure container or a hot water tank. The time for immersing the molded body in reduced pressure water or boiling water is preferably 3 minutes or more, more preferably 8 minutes or more, and even more preferably 20 minutes or more in order to promote water absorption. The upper limit of the immersion time is preferably 60 minutes, more preferably 45 minutes in order to increase the compressive strength of the hardened cement body.

[0091] In the water absorption step, when the cement composition does not contain coarse aggregate, the water content in the hardened molded body having a diameter of 50 mm and a height of 100 mm is taken as 100 volume %, and is preferably 0.2 volume % or more, more preferably 0.3 to 2.0 volume %, and even more preferably 0.35 to 1.7 volume %. When the cement composition contains coarse aggregate, the water content in the hardened molded body having a diameter of 100 mm and a height of 200 mm is taken as 100 volume %, and is preferably 0.2 volume % or more, more preferably 0.3 to 2.0 volume %, and even more preferably 0.35 to 1.7 volume %.

[0092] If the water absorption rate is 0.2 volume % or more, the compressive strength of the hardened cement paste is higher.

[0093] (Characteristics of hardened cement) The hardened cement product of the present invention obtained by the above-mentioned manufacturing method has high compressive strength and is therefore less susceptible to cracks, etc. In addition, the hardened cement product can be used to reduce the weight of components, for example by reducing their thickness, and can also improve workability.

[0094] The hardened cement body of the present invention also has excellent abrasion resistance. For example, the abrasion depth of the hardened cement body after 60 minutes, measured in accordance with "ASTM C779", is preferably 0.5 mm or less, more preferably 0.4 mm or less, and even more preferably 0.3 mm or less. Since the abrasion depth of the hardened cement body is 0.5 mm or less, it has the abrasion resistance required for a hardened cement body for paving.

[0095] Furthermore, the hardened cement body of the present invention is excellent in water impermeability, freeze-thaw resistance, and salt impermeability.

[0096] In addition, the hardened cement body of the present invention has excellent dimensional stability. For example, the shrinkage strain of a 40×40×160 mm test piece of the hardened cement body measured in accordance with JIS A 1129-2:2010 "Method for measuring change in length of mortar and concrete - Part 2: Contact gauge method" after storage for six months is preferably 10×10 -6 Less than or equal to 8×10 -6 Less than 6×10, more preferably -6 The following is the result.

[0097] [Example] Examples and comparative examples using the method for producing a hardened cement body will be described below, but the present invention is not limited to these examples.

[0098] (Preparation of test specimen) First, the cement composition before casting was mixed and cast into a formwork to obtain an unhardened molded body. The unhardened molded body was cured and then demolded to obtain a hardened molded body. Next, the hardened molded body was immersed in water for 30 minutes in a depressurized desiccator. For the depressurization, an "Aspirator (AS-01)" manufactured by AS ONE Corporation was used. After immersion, the molded body was steam-cured at 90°C for 48 hours as a heat curing process. After cooling to 20°C, the molded body was heated at 180°C for 48 hours as a high-temperature heating process. In this manner, test specimens for each example and each comparative example were prepared.

[0099] The cement compositions in each of the examples and comparative examples are as shown in Figure 2. The "spheroidized" description for the cement in Example 10 indicates that the cement has been subjected to a polishing treatment. For the polishing treatment, a high-speed airflow agitator, trade name "Hybridizer NHS-3 type" (manufactured by Nara Machinery Works, Ltd.), was used.

[0100] The cement used was low-heat Portland cement (manufactured by Taiheiyo Cement Corporation). The cement that was not polished had a Blaine specific surface area of ​​3320 cm 2 / g, and the 50% weight cumulative particle size was 15.6 μm. The polished cement had a Blaine specific surface area of ​​2350 cm 2 / g and the 50% weight cumulative particle size was 15.1 μm.

[0101] Silica fume has a BET specific surface area of ​​18m 2 / g was used. Silica powder was used as the inorganic powder. The silica powder had a maximum particle size of 12 μm, a 50% volume cumulative particle size of 2 μm, and a 95% volume cumulative particle size of 5.8 μm.

[0102] Tap water was used. The fine aggregate used was silica sand, with a maximum particle size of 1.0 mm, 98% by mass of the sand being 0.6 mm or less, 45% by mass of the sand being 0.3 mm or less, and 3% by mass of the sand being 0.15 mm or less.

[0103] The hard sands used were garnet sand, quartz, alumina, silicon carbide, and granite. The garnet sand had a new Mohs hardness of 10 and a maximum grain size of 1.2 mm. The quartz had a new Mohs hardness of 8 and a maximum grain size of 4.7 mm, with 11.5% of the grains being 4.7-4.0 mm, 17% being 4.0-3.35 mm, 32% being 3.35-2.8 mm, 28.2% being 2.8-2.36 mm, and 9.2% being 2.36-2.0 mm. The alumina had a new Mohs hardness of 12 and a maximum grain size of 3.3 mm, with 20% or more by mass being 3.3-2.4 mm, 45% or more by mass being 2.4-2.0 mm, and 70% or more by mass being 2.4-1.7 mm. The silicon carbide had a new Mohs hardness of 13, a maximum grain size of 4.0 mm, 20% or more by mass of grains between 4.0-2.8 mm, 45% or more by mass of grains between 2.8-2.4 mm, and 70% or more by mass of grains between 2.4-2.0 mm. The granite had a new Mohs hardness of 7, and met the grain size specified for crushed sand in JIS A5005 "Crushable stone and crushed sand for concrete." In addition, the 10% cumulative grain size by weight of each hard sand was 1.2 mm or more, and the 90% cumulative grain size by weight was 5.0 mm or less.

[0104] In this specification, the 10% and 90% weight cumulative particle sizes of hard sand refer to the particle sizes at which the particles reach 10% and 90% by weight of the total particles when they are accumulated in order from the smallest particle size.

[0105] Crushed stone was used as the coarse aggregate, with a maximum particle size of 20 mm. The high-performance water reducing agent used was a polycarboxylic acid-based high-performance water reducing agent with the product name "Floric SF500U" (manufactured by Floric Co., Ltd.) The polycarboxylic acid-based high-performance water reducing agent had a solid content of 27.4 mass%.

[0106] The antifoaming agent used was "Master Air 404" (BASF Japan). The fibers used were steel fibers having a diameter of 0.2 mm and a length of 15 mm.

[0107] (test) For each of the examples and comparative examples, the flow value, compressive strength, abrasion depth, and shrinkage strain were measured.

[0108] The flow value was measured using the method described in "11. Flow test" of JIS R 5201 "Physical test methods for cement", omitting the 15 drop motions, and the zero-drop flow value was measured. In addition, using the method described in JIS A 1150:2007 "Slump flow test method for concrete", the diameter that was thought to be the largest after the concrete stopped moving and the diameter in the perpendicular direction were measured.

[0109] The compressive strength of the mortar after curing was measured in accordance with "JSCE G 505-2018 (Draft method for testing compressive strength of mortar or cement paste using cylindrical specimens)".

[0110] The abrasion depth was measured by preparing a test specimen of 30 x 30 x 6 cm and measuring the abrasion depth after 60 minutes in accordance with ASTM C779.

[0111] The shrinkage strain was measured by manufacturing 40 x 40 x 160 mm test specimens and burying an embedded type strain gauge (Tokyo Measuring Instruments Laboratory KM-30) and a thermocouple in the centre of the test specimen in accordance with the Autogenous Shrinkage Test Method (Draft) of the Japan Concrete Institute (Report of the Research Committee on Super-Fluid Concrete (II), Japan Concrete Institute, 1994).

[0112] Each example and each comparative example was evaluated according to the criteria shown in the following Table 1. In addition, the results were rated as very good (A), good (B), pass (C), or fail (E). [Table 1]

[0113] The results of various measurements for each of the Examples and Comparative Examples are shown in Table 2 below. [Table 2]

[0114] The examples were rated as pass (C) or better in terms of flow value, compressive strength, abrasion depth, and shrinkage strain. Also, in example 7, in which silicon carbide was mixed at 70% relative to the total amount of fine aggregate and hard sand, the abrasion depth was rated as very good (A), so it can be said that, among quartz, alumina, and silicon carbide, silicon carbide in particular improves wear resistance.

[0115] In Examples 8 and 9, in which coarse aggregate was added, the evaluation of shrinkage strain was very good (A), so it can be said that adding coarse aggregate further improves dimensional stability. Also, in Example 10, in which two types of hard sand, alumina and silicon carbide, were used, the evaluation of wear depth and shrinkage strain was also very good (A), so it can be said that using two or more types of hard sand further improves abrasion resistance and dimensional stability.

[0116] In Example 11, in which the cement was polished, the compressive strength and abrasion depth were rated as extremely good (A), which indicates that polishing the cement improves the compressive strength and abrasion resistance. In Example 12, in which 3% fiber was included, the compressive strength and abrasion depth were rated as extremely good (A). In Example 13, in which 4% fiber was included, not only the compressive strength and abrasion depth but also the shrinkage strain was rated as extremely good (A). Therefore, it can be said that the inclusion of fiber improves the compressive strength, abrasion resistance, and dimensional stability.

[0117] In contrast, the comparative example was rated as failing (E) in any of the flow value, compressive strength, abrasion depth, and shrinkage strain.

[0118] From the above, the hardened cement product of the present invention not only satisfies the abrasion resistance required for paving hardened cement products, but also has the fluidity of the cement composition suitable for application, and therefore has sufficient application and filling properties when applying the cement. [Explanation of symbols]

[0119] 10 Polishing treatment device 11 Rotor 12 Blades 13 Circulation circuit 13a Circulation circuit inlet 13b Circulation circuit outlet 14 Inlet 15 Outlet 16 Stator 17 Collision chamber 18 On-off valve 19 Exhaust valve

Claims

1. A hardened product of a cement composition comprising at least cement, silica fume, an inorganic powder, a fine aggregate, hard sand, a high-performance water reducing agent, a defoaming agent, and water, Compressive strength: 300N / mm 2 That's all. The maximum particle size of the fine aggregate is 1.2 mm or less, The hardness of the hard sand is higher than the hardness of the fine aggregate, The grain size of the hard sand is such that the 10% weight cumulative grain size is 1.2 mm or more and the 90% weight cumulative grain size is 5.0 mm or less; A hardened cement body, characterized in that the content of said hard sand relative to the total amount of said fine aggregate and said hard sand is 30% or more and 70% or less.

2. 2. The hardened cement product according to claim 1, further comprising coarse aggregate having a maximum particle size of more than 2.5 mm and not more than 20 mm.

3. 3. The hardened cement product according to claim 1, wherein the hard sand has a new Mohs hardness of 8 or more.

4. 4. The hardened cement product according to claim 1, wherein the hard sand is one or more types selected from the group consisting of quartz, alumina, and silicon carbide.

5. The cement comprises ground particles of medium-heat or low-heat Portland cement; The polished particles have a 50% cumulative particle size by volume of 10 to 18 μm; Blaine specific surface area is 2100-2900 cm 2 The hardened cement product according to any one of claims 1 to 4, characterized in that the hardened cement product has a molecular weight of 1 / g.

6. The hardened cement body according to any one of claims 1 to 5, comprising one or more types of fibers selected from metal fibers, organic fibers, and carbon fibers, and the fiber content is 4 volume % or less.

7. A precast concrete slab comprising the hardened cement body according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Alumina cement and castable refractory by using the same

    JP1999322380A

  • Fine aggregate, mortar and cement concrete

    JP2004091305A

  • Concrete pavement

    JP2016179927A

  • Member for protection work of road or railroad, and method for producing the same

    JP2017226547A

  • Mortar composition, spraying method, and manufacturing method of cured article

    JP2019172494A